ACHIEVEMENTS, INNOVATIONS, TECHNOLOGIES AND DEVELOPMENT PROSPECTS OF AGRICULTURAL SCIENCE AND TEXTILE INDUSTRY (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
ABSTRACTThis article explores the significant advancements, innovations, and technologies in agricultural science and the textile industry, highlighting their interdependence and potential for future development. The focus is on how modern agricultural practices and technological innovations contribute to the evolution of the textile industry, with particular emphasis on sustainable practices, biotechnology, and digital transformation. The paper also discusses the prospects for future development, aiming to provide insights into the potential trajectories of these sectors.